The discovery/justification context dichotomy within formal and computational models of scientific theories: a weakening of the distinction based on the perspective of non-monotonic logics - Morales Delgado, Jorge A. (2017)
The present paper analyses the topic of scientific discovery and the problem of the existence of a logical framework involved in such endeavour. We inquire how several non-monotonic logic frameworks and other formalisms can account for such a task. In the same vein, we analyse some key aspects of the historical and theoretical debate surrounding scientific discovery, in particular, the context of discovery and context of justification context distinction. We present an argument concerning the weakening of the discovery/justification context dichotomy based on the descriptive accent contained in the non-monotonic logic perspective together with its epistemological concerns.